(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Diseases are caused by various reasons. Faulty habits of taking food is one among them but it has great importance because it directly affects normal body mechanisms. So everyone must have to learn how to eat? When to eat? How much quantity? Where to eat? and many more things. Answer to these questions varies according to individuals. Everyone should try to find out it by knowing the basic principles for intake of Aahara. These principles are described in Ayurveda which is applicable in every kaala. So here tried to elaborate such principle of Ayurveda known as Aahar Vidhi Vidhan.